2017 IEEE International Conference on Robotics and Automation (ICRA) 2017
DOI: 10.1109/icra.2017.7989790
|View full text |Cite
|
Sign up to set email alerts
|

A cable-based series elastic actuator with conduit sensor for wearable exoskeletons

Abstract: Abstract-There is currently a scarcity of wearable robotic devices that can practically provide physical assistance in a range of real world activities. Soft wearable exoskeletons, or exosuits, have the potential to be more portable and less restrictive than their rigid counterparts. In this paper, we present the design of an actuation system that has been optimized for use in a soft exosuit for the human arm. The selected design comprises a DC motor and gearbox, a flexible cable conduit transmission, and a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In cable-based RAS, a rope or a cable mechanically connects the actuation unit to the output. Most of the reviewed RAS use Bowden cables consisting of a cable guided in a sheath (Letier et al, 2006 ; Veneman et al, 2007 ; Kong et al, 2009 ; Wang et al, 2009 ; Vitiello et al, 2013 ; Agarwal et al, 2015 ; Asbeck et al, 2015 ; Bartenbach et al, 2015 ; Cempini et al, 2015 ; In et al, 2015 ; Nycz et al, 2015 , 2016 ; Cappello et al, 2016 ; Choi et al, 2016 ; Choi et al, 2019 ; Dinh et al, 2016 ; Kalantari and Ghaffari, 2016 ; Norman et al, 2016 ; Xiloyannis et al, 2016 , 2019 ; Blumenschein et al, 2017 ; Jeong and Cho, 2017 ; Popov et al, 2017 ; Yun S.-S. et al, 2017 ; Randazzo et al, 2018 ; Yi et al, 2018 ; Burns et al, 2019 ; Dwivedi et al, 2019 ; Tran et al, 2020 ). Electrical motors are most commonly used to actuate the cable transmission.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In cable-based RAS, a rope or a cable mechanically connects the actuation unit to the output. Most of the reviewed RAS use Bowden cables consisting of a cable guided in a sheath (Letier et al, 2006 ; Veneman et al, 2007 ; Kong et al, 2009 ; Wang et al, 2009 ; Vitiello et al, 2013 ; Agarwal et al, 2015 ; Asbeck et al, 2015 ; Bartenbach et al, 2015 ; Cempini et al, 2015 ; In et al, 2015 ; Nycz et al, 2015 , 2016 ; Cappello et al, 2016 ; Choi et al, 2016 ; Choi et al, 2019 ; Dinh et al, 2016 ; Kalantari and Ghaffari, 2016 ; Norman et al, 2016 ; Xiloyannis et al, 2016 , 2019 ; Blumenschein et al, 2017 ; Jeong and Cho, 2017 ; Popov et al, 2017 ; Yun S.-S. et al, 2017 ; Randazzo et al, 2018 ; Yi et al, 2018 ; Burns et al, 2019 ; Dwivedi et al, 2019 ; Tran et al, 2020 ). Electrical motors are most commonly used to actuate the cable transmission.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, in Hofmann et al ( 2018 ) and Jeong and Cho ( 2017 ), bending angle sensors combined with dynamic feed-forward friction compensation were presented, such that no sensors were needed at the output. Often, series elastic elements (SEE) have been used to measure the force transmitted by Bowden cables at the output (Agarwal et al, 2015 ; Blumenschein et al, 2017 ; Marconi et al, 2019 ). SEE have also been used to pretension the wires and make the transmission more compliant (Veneman et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With reference to seminal wrist assessment studies [7,8,12] and rehabilitation devices [11,15,16], we identified the following requirements as paramount to develop a 2-DOF wrist stiffness and range of motion assessment device: 1) increase range of motion, 2) increase torque output, and 3) incorporate direct torque measurement. A Bowden cable-based actuation scheme, which locates the motors off-board as used in [17,18], was adopted for increased device range of motion and torque output. However, the benefits of using Bowden cables comes at the cost of reduced accuracy in torque measurement and control.…”
Section: Series Elastic Actuation For a 1-dof Wrist Modulementioning
confidence: 99%